THE INFLUENCE OF WORKLOAD AND MOTIVATION ON EMPLOYEE SATISFACTION AND PERFORMANCE OF PT GEMA SOERYA SAMODRA - Teddy Adrianto; Zainal Ilmi; Ariesta Heksarini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to determine the effect of workload and motivation on employee satisfaction and performance (a study in the employees of PT Gema Soerya Samodra). With good quality human resources, it is hoped that the company's performance will be better and optimal. But of course, to achieve optimal performance, we often encounter various obstacles so that sometimes the desired results are not achieved. The population in this study were employees of PT Gema Soerya Samodra, the sample in this study were 40 employees. Methods of data collection are carried out by distributing questionnaires or questionnaires to respondents who become the research sample. This study uses data analysis tools, namely the validity and reliability tests, so this study uses the partial least square (PLS) analysis method. The tools used in data processing use the PLS Smart program. The results show that 1)Workload positive and significant effect on satisfaction, 2) Motivation positive and significant effect on satisfaction, 3) Workload positive and significant effect on performance, 4) Motivation has a positive and significant effect on performance, 5) satisfaction has a positive and significant effect on performance. Keywords: Workload, Satisfaction, Motivation, Performance.